Phylogenetic Groups and Antimicrobial Resistance among Uropathogenic Escherichia coli Isolates from Hospitalized Patients in Tehran - Mana Talebi Farahani; Mohammad Karim Rahimi; Mehdi Goudarzi (Novelty in Biomedicine, 2025)
Background: The presence of Escherichia coli among uropathogens is increasing significantly worldwide. It accounts for a considerable amount of morbidity and high medical costs and also can lead to mortality. The current research aims to investigate E. coli antimicrobial susceptibility patterns and the molecular causes of E. coli resistance trends and virulence factors among phylogenetic groups of Uropathogenic Escherichia coli (UPEC) in Urinary tract infection (UTI) patients in a hospital in Tehran, Iran. The antimicrobial susceptibility of urinary E. coli isolates.